The Intention of Empowering Excellence on the Path to Professional Qualification in Sustainable Development and Governance - Azleen binti Ilias; Nasrudin Bin Baidi; Fazlida binti Mohd Razali; Rahida binti Abdul Rahman (Accounting Research Institute (ARI), Universiti Teknologi MARA (UiTM), 2023)
This study examined the influence of perceptions related to prestige/status, job security/stability, opportunity for advancement, program difficulty, and salary on the intention to pursue the Certified Internal Auditor (CIA) Qualification among students in public and private universities. Based on the Theory of Planned Behavior (TPB), this study employed collecting data using a questionnaire survey that consists of 243 Bachelor of Accounting students from 11 Malaysian higher learning institutions. The findings indicated that perceptions of prestige/status, opportunity for advancement, and program difficulty significantly impacted the intention to pursue the CIA Qualification. Participants display a positive perception of the credibility and reputation of the CIA exam and career. The findings offer insights for educators and practitioners to foster stronger collaborations between universities and the Institute of Internal Auditors Malaysia (IIAM), facilitating tailored curriculum and activities to promote long-term corporate sustainability. The results showed that having a professional qualification is critical for enabling individuals to succeed in sustainable governance and its ability to equip individuals to become successful change agents that aligned with the Sustainable Development Goal (SDG) 4.